2022
DOI: 10.1002/joc.7745
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric circulation types controlling rainfall in the Central American Isthmus

Abstract: Rainfall mechanisms in the Central American Isthmus are controlled by complex physical interactions across spatial and temporal scales, which are reflected on the dynamics of atmospheric circulation patterns affecting the region. However, physical mechanisms and their relationships with thermodynamic distributions connected to overturning circulations remain elusive. Here, a set of six recurrent daily atmospheric patterns, or weather types (WT), is defined using a k-means++ clustering algorithm on standardized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 113 publications
4
15
0
Order By: Relevance
“…Mexico's National Meteorological Service (SMN, in Spanish) maintains the national climatological database for Mexico, integrated into the Climate Computing project (CliCom). This project consists of a quality‐controlled data set using Climate Computing software developed by the United Nations Organization and incorporated into the data set by Dunn et al (2020) (Sáenz et al, 2023). Observations at each of the 5459 meteorological stations in the country are recorded daily at 0800 LST (local standard time).…”
Section: Methodsmentioning
confidence: 99%
“…Mexico's National Meteorological Service (SMN, in Spanish) maintains the national climatological database for Mexico, integrated into the Climate Computing project (CliCom). This project consists of a quality‐controlled data set using Climate Computing software developed by the United Nations Organization and incorporated into the data set by Dunn et al (2020) (Sáenz et al, 2023). Observations at each of the 5459 meteorological stations in the country are recorded daily at 0800 LST (local standard time).…”
Section: Methodsmentioning
confidence: 99%
“…The clustering analysis was performed using the k-means procedure of MacQueen (1967). Weather patterns of single days were assigned to the cluster to which the Euclidean distance was lowest (Zhang and Villarini 2019, Zhang et al 2022, Saenz et al 2023. To accurately determine the final number of regimes, we employed a two-step procedure.…”
Section: Circulation Type Classificationmentioning
confidence: 99%
“…Reviews of these climate precursors can be found in and Maldonado et al (2016). In Sáenz et al (2023), an analysis of the atmospheric circulation types controlling rainfall in Central America is presented. Table 1 summarizes the characteristics of a non-exhaustive list of mesoscale to large-scale mechanisms acting in the region.…”
Section: Climate Change In Climatology In Central America Driving La...mentioning
confidence: 99%
“…Observational climate data across Central America vary largely by country (Sáenz et al, 2023). However, even in areas with better coverage, it is sparse and often contains large gaps in time series.…”
Section: Data Networking and Dissemination In The Regionmentioning
confidence: 99%